Vroom's Theories in School Leadership - Mmalefikane Sylvia SEPENG (Social Sciences and Education Research Review)
This article explores school leadership through the lens of Victor Vroom's expectancy theory, contextualized within the Fourth Industrial Revolution (4IR). It examines how Vroom's insights on motivation and decision-making can be applied to educational leadership in an era of rapid technological change. The analysis focuses on four key themes